ANALYSIS OF THE EFFECT OF NON-CASH PAYMENT TRANSACTIONS ON THE MONEY SUPPLY M1 IN INDONESIA - Umairoh, Novita; Wijaya, Riko Setya (Yayasan Education and Social Center, 2023)
The rapid development of science and technology encourages various innovations in the financial sector. The payment system has evolved from a cash payment system to a non-cash payment system. The convenience offered by the non-cash payment system will impact the effectiveness of monetary policy and financial stability through the money supply in the community. This study aims to determine the impact of non-cash payments on the narrow money supply in Indonesia. This study was conducted using secondary time series semester data sourced from Bank Indonesia (BI) and the Central Bureau of Statistics (BPS) with a period between 2016 (I) and 2022 (II). The data is processed using multiple linear regression analysis methods. The results of this study will show that transactions using debit cards have no significant effect on the narrow money supply, while transactions using credit cards have no significant effect on the little money supply, and e-money has a positive significant impact on the limited money supply in Indonesia